Living Law in Modern Legal Systems: Challenges to the Principle of Legality - Valerina, Anindita Tresa; Rismana, Daud (Walisongo Law Review (Walrev), 2024)
The transformation of the principle of legality in Article 1 paragraph (1) of the new Criminal Code and the incorporation of living law in Article 2 highlights a pivotal shift in Indonesia's legal framework. Indonesia, adhering to a civil law system, emphasizes that crimes and punishments are governed solely by statutory provisions. The principle of legality ensures that no act can be deemed criminal without a written law. However, the inclusion of living law, an unwritten customary law rooted in societal traditions, challenges this principle. This transformation, motivated by the decolonization of the Dutch-inherited Criminal Code, raises critical questions about legal certainty and the adaptability of customary law within a modern legal system. This study aims to analyze the juxtaposition of Article 1 and Article 2 in the new criminal code. Using a normative-conceptual approach and library research, the study examines statutory frameworks and the socio-legal dynamics surrounding these provisions. Findings reveal that while the previous Criminal Code lacked recognition of living law, the new criminal code incorporates it as an extension of the legality principle. However, this integration has sparked significant debate due to the inherent uncertainty of customary law, which contrasts with the clear and definitive requirements of lex certa. Customary law prioritizes community justice by adapting to time, place, and circumstances, yet its application risks undermining the predictability demanded by the principle of legality. In conclusion, the coexistence of statutory legality and living law in the new criminal code underscores a complex legal reform balancing modern legal certainty with Indonesia's pluralistic traditions. Transformasi asas legalitas dalam Pasal 1 ayat (1) Kitab Undang-Undang Hukum Pidana dan masuknya hukum yang hidup (living law) dalam Pasal 2 menyoroti adanya perubahan penting dalam kerangka hukum pidana. Indonesia yang menganut sistem hukum Eropa menekankan bahwa kejahatan dan hukuman hanya diatur oleh ketentuan undang-undang. Asas legalitas menjamin bahwa suatu perbuatan tidak dapat dianggap pidana tanpa adanya hukum tertulis. Namun, dimasukkannya hukum yang hidup, yaitu hukum adat tidak tertulis yang berakar pada tradisi masyarakat, menantang prinsip ini. Transformasi yang dilatarbelakangi oleh dekolonisasi KUHP warisan Belanda ini menimbulkan pertanyaan kritis mengenai kepastian hukum dan kesesuaian hukum adat dalam sistem hukum modern. Penelitian ini bertujuan untuk menganalisis penjajaran Pasal 1 dan Pasal 2 dalam KUHP baru. Dengan menggunakan pendekatan normatif-konseptual dan studi kepustakaan, studi ini mengkaji kerangka perundang-undangan dan dinamika sosial-hukum yang melingkupi ketentuan tersebut. Temuan menunjukkan bahwa meskipun KUHP sebelumnya kurang mengakui hukum yang hidup, KUHP yang baru memasukkannya sebagai perpanjangan dari asas legalitas. Namun, integrasi ini telah memicu perdebatan yang signifikan karena ketidakpastian hukum adat, yang kontras dengan persyaratan lex certa yang jelas dan definitif. Hukum adat mengutamakan keadilan masyarakat dengan menyesuaikan diri dengan waktu, tempat, dan keadaan, namun penerapannya berisiko melemahkan prediktabilitas yang dituntut oleh asas legalitas. Kesimpulannya, keberadaan legalitas undang-undang dan hukum yang hidup dalam KUHP yang baru menggarisbawahi adanya reformasi hukum yang kompleks yang menyeimbangkan kepastian hukum modern dengan tradisi pluralistik di Indonesia.